Ortho versus Meta Chlorophenyl-2,3-Benzodiazepine Analogues: Synthesis, Molecular Modeling, and Biological Activity as AMPAR Antagonists - Qneibi, Mohammad (ACS Omega, 2020)
[Image: see text] 2,3-Benzodiazepine compounds are an important family of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) antagonists that act in a noncompetitive manner. Due to the critical role of AMPARs in the synapse and various neurological diseases, significant scientific interest in elucidating the molecular basis of the function of the receptors has spiked. The analogues were synthesized to assess the functional consequence of removing the amine group of the phenyl ring, the potency and efficacy of inhibition by substituting a halogen group at the meta vs ortho position of the phenyl ring, and layout the prediction of potential drug candidates for AMPAR hyperactivation. Using the whole-cell patch-clamp technique, we assessed the effect of the derivative on the amplitude of various AMPA-type glutamate receptors and calculated the desensitization and deactivation rates before and after treatment of HEK293 cells. We noticed that the amino group is not necessary for inhibition as long as an electron-withdrawing group is placed on the meta position of the phenyl ring of BDZ. Furthermore, compound 4a significantly inhibited and affected the desensitization rate of the tested AMPARs but showed no effect on the deactivation rate. The current study paves the way to a better understanding of AMPARs and provides possible drug candidates of 2,3-BDZ different from the conventional derivatives.